Nitrogen contribution and microbial community of size-fractionated anammox sludge in continuous stirred-tank reactors. (October 2022) - Zhang, Qi; Zhao, Leizhen; Zhang, Jiaqi; Liu, Wenru; Cai, Shu; Chen, Liwei; Cai, Tianming; Ji, Xiao-Ming
Graphical abstract: Highlights: Proper particle size (<1 mm) contributed to 93 % of the nitrogen removal rate. Ca. Kuenenia's relative abundance in granules was 2.3 times of that in fine sludge. Microbial diversity shifts into a simpler model as the granular sizes increase. Fine sludge might be the potential major source of NO/N2 O production. Abstract: In this study, the microbial diversity of size-fractionated anammox sludge in a well-mixed system and their contribution to nitrogen transformation were investigated. Results showed that small granules (0.2–1.0 mm) contributed to the major part of the nitrogen removal rate (56 %) due to its largest mixed liquor volatile suspended solids (1240 ± 80 mg·L −1 ). However, large granules (>1.0 mm) possessed the highest relative abundances of Ca. Kuenenia stuttgartiensis and specific anammox activity, representing 49.34 % and 24.45 ± 0.01 mg-N·g −1 -mixed liquor volatile suspended solids·h −1, respectively. The microbial diversity decreased as the increase of granular size, resulting in microbial community shifting to a simpler model. Metagenomic analysis showed that fine sludge might be the potential major for NO/N2 O production in the mature well-mixed system under inorganic conditions. This study provides guidance for the evaluation of nitrogen contribution by anammox size-fractionated sludge and the inhibition of the potential NO/N2 O emission in anammox processes.